New Access to Pyrano[2,3-c]pyrazole-3-carboxylates via Domino Four-Component Reaction and Their Antimicrobial Activity - Muhammad Siddiq Maarop; Fatin Nur Ain Abdul Rashid; Mohd Fazli Mohammat; Zurina Shaameri; Saiful Azmi Johari; Mazurah Mohamed Isa; Anis Low Muhammad Low (Indonesian Journal of Chemistry, 2020)
A library of some novel classes of pyrano[2,3-c]pyrazole-3-carboxylates was synthesized by employing uncatalyzed domino four-component reaction using diethyloxaloacetate, hydrazine hydrate, aldehydes and malononitrile in refluxing of ethanol-acetic acid solvent systems. Series of domino reactions involving of pyrazolone formation, Michael addition, and Thorpe-Ziegler cyclization reaction managed to produce the cyclized products from moderate to excellent yield. This protocol provides a reliable, general and salient procedure for the title compound using a one-pot approach. Preliminary biological screening unveiled limited potentials of this class of compounds for antimicrobial lead compound due to its limited solubility properties.